VOCATIONAL HIGH SCHOOLS STUDENTS’ VIEWS ON THE CIRCULATION OF THE ELECTRIC CURRENT IN THE ELECTRONIC CONTROL UNIT (ECU) OF THE MODERN CARS - Kaltsas, Apostolos (PUPIL: International Journal of Teaching, Education and Learning, 2020)
An electronic control unit (ECU) is any embedded system in automotive electronics that controls one or more of the electrical systems or subsystems in a vehicle. Its purpose is to control and process information by converting it into electrical signals to be recognized. This paper presents the results of research on students' views on how the ECU electrical signals of modern cars are represented in their minds and what mental current model they adopt. The literature on students' views about electric current states that they adopt 4 models: The monopolar model, the conflicting currents model, the consumer model, and the scientific model, which is the scientifically accepted. The survey was conducted through a semi-structured interview where respondents were free to talk about the issue and give their views. 26 students (21 boys and 5 girls) of Vocational High Schools (specialty "Vehicle Technician") from the prefecture of Attica participated. The analysis of the results showed that 15.4% of the students adopted the monopolar model, 30.8% the conflicting currents model, 26.9% the consumer model while the same percentage (26.9%) adopted the scientific model where it turns out that the scientific model approach does not seem to be achieved satisfactorily. It was also found that students' views were influenced by their previous knowledge and experiences with other modern devices such as mobile phones. In conclusion, it is imperative that teachers, by designing appropriate teaching interventions, inspire and guide students in intensifying their study of the characteristics of CPU electrical signals in order to increase their interest and approach to the scientific model.